Studi In Silico Senyawa Bioaktif dalam Madu Tradicia cochinchinensis terhadap SARS-CoV-2 - Azizah Risani Rusnel; Fitri Amelia (Lembaga Yasin AlSys, 2026)
The COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has highlighted the urgent need for effective antiviral agents. Natural products have increasingly attracted attention as potential sources of antiviral compounds due to their structural diversity and relatively favorable safety profiles. This study aimed to evaluate the antiviral potential of bioactive compounds present in Tradicia cochinchinensis honey against the main protease (3CLpro) of SARS-CoV-2 using an in silico approach. Molecular docking procedures were performed on the 3CL protease (PDB ID: 6M2N) and subsequently validated using root mean square deviation (RMSD) analysis. Drug-likeness and pharmacokinetic suitability were assessed based on Lipinski’s Rule of Five and ADMET predictions. Among the 17 compounds tested, luteolin, genistein-O-glucoside, and ellagic acid exhibited the lowest binding free energies (−7.94, −7.74, and −6.11 kcal/mol, respectively), which were comparable to the reference compound ritonavir. Luteolin and ellagic acid showed stable binding conformations with RMSD values below 2 Å, whereas genistein-O-glucoside demonstrated slightly higher conformational flexibility. Further evaluation indicated that luteolin fulfilled Lipinski’s criteria and possessed a more favorable ADMET profile than the other compounds. These findings suggest that luteolin is the most promising candidate among the compounds investigated as a potential inhibitor of the SARS-CoV-2 3CL protease, although validation of its antiviral activity and safety still requires additional in vitro and in vivo investigations.